PENGARUH PENDEKATAN CONCEPTUAL PROBLEM SOLVING (CPS) TERHADAP KEMAMPUAN REPRESENTASI DAN PEMECAHAN MASALAH FISIKA SISWA - Saputra, Herdiansyah; Mansyur, Jusman; Supriyatman, Supriyatman (Universitas Tadulako, 2021)
This study aims to determine the effect of a conceptual problem solving (CPS) approach on students' physics representation and problem-solving abilities. The research design was a quasi experiment with a pretest-posstest nonquivalent group design. The study population was all students of Class XI MIA SMA Negeri 2 Palu. The sampling technique was purposive sampling. Class XI MIA 1 as the experimental class and Class XI MIA 2 as the control class. Data analysis using t-test using SPSS 22.0 application at a significance level of 0.05 with the prerequisite test for normality and homogeneity. The results of the statistical test of representation ability obtained Sig. = 0,000 and problem-solving Sig. = 0.000 with criteria to accept Ho if Sig. > 0.05 and reject H0 if Sig. <0.05. Sig value. <0.05 so that Ho is rejected with the conclusion that there is an effect of the conceptual problem solving (CPS) approach on students' physics representation and problem-solving abilities.